Hiring through referrals in a labor market with adverse selection - Aurelie Dariel; Arno Riedl; Simon Siegenthaler (Center for Economic Studies and ifo Institute (CESifo), 2019)
Information asymmetries can prevent markets from operating efficiently. An important example is the labor market, where employers face uncertainty about the productivity of job candidates. We examine theoretically and with laboratory experiments three key questions related to hiring via referrals when employees have private information about their productivity. First, do firms use employee referrals when there are social ties between a current employee and a future employee? Second, does the existence of social ties and hiring through employee referrals indeed alleviate adverse selection relative to when social ties do not exist? Third, does the existence of social ties have spill-over effects on wages and hiring in competitive labor markets? The answers to all three questions are affirmative. However, despite the identified positive effect of employee referrals, hiring decisions fall short of the (second-best) efficient outcome. We identify risk aversion as a potential reason for this.
Keywords: C92; D82; D85; E20; 330; adverse selection; labor market; employee referrals; social networks